A low-cost system for the study of proteins used in salmonid diets, use of proteolysis to determine the quality. (1st August 2022) - Parodi, Jorge; Herrera, Hector; Sanchez, Rodrigo; Effer, Brian
Abstract: A proteolysis system, a classic biochemistry model, is proposed to enable the feasibility of indirectly assessing the quality of protein present in salmonid diets like screening system. An artificial gastric solution was developed with pepsinogen commercial, the volume of a salmonid stomach was estimated, and 8 g of food was mixed per 50 ml of solution, which was constantly stirred for 3 h and kept at 15 °C constant. We note that this artificial gastric solution requires pepsin to degrade samples, which occurs at pH 2.0, in addition, proteolysis depends on time and temperature. Comparing albumin, food and a standard mixture of proteins could observe varying degrees of fragmentation. The results suggest a low-cost system to evaluate the source of a protein, by correlated the number of fragments generated, an indicator of the quality of the protein. In addition, it allows evaluating mixtures with the disposition of the protein to be proteolyzed. The present protocol can be used for screening protein before to in vivo test and after of digestibility test or in support of digestibility protocol for improve nutrition study. Highlights: Take the traditional biochemistry proteolysis for improve the actual protocol for control de protein and diet for salmon We demonstrate the used of pepsinogen, from commercial source can used for screening of quality of the protein We show the relation between proteolysis approach and cells growth. Suggested a in vitro study previous to in vivo complex study The protocol, are ore faster low cost and help to take decision about new protein, diet before to use in animal study